Evolution and development of technology transfer models and the influence of knowledge-based view and organizational learning on technology transfer. - Raduan Che Rose; Sazali Abdul Wahab; Jegak Uli; Haslinda Abdullah (2009)
The main objective of this paper is to review the evolution and development of technology transfer models before and after the 1990s. These technology transfer models will be reviewed in terms of focus of each model, strengths and limitations of the models, and to highlight the significance influence of knowledge-based view and organizational learning perspectives, which have strong theoretical foundation, on the current technology transfer models. The early technology transfer models were developed to govern the implementation of technology transfer activities and their application to market place; where emphasis was given on the promotion, adoption and diffusion of new innovations and technologies to potential users as well as on technology transfer processes. Nonetheless, with the emergence of knowledge-based economies, the technology transfer models have been gradually developed by management researchers to explain the dynamic role of knowledge underlying technology as the organizations’ strategic asset and organizational learning through inter-firm technology transfer.